Teacher Professional Development Needs in Using Digital Technology for Quality of Education - Maimun Maimun; Mohammad Viktor Farid Hakim (AL-ISHLAH: Jurnal Pendidikan, 2021)
The research aims to obtain the professional development model needs of teachers in mastering digital technology to improve the quality of education. Technology development in education has forced all parties to integrate various educational activities according to current conditions. The research method used mixed research involving qualitative and quantitative data analysis. Data were collected through a survey which was completed with observation and interviews. Analysis of qualitative data is in the form of narrative through data reduction, data presentation, and concluding stages. In contrast, quantitative data is the result of digital technology needs presented in percentages. The analysis results show that digital technology is still not fully used in teaching and learning activities. This also impacts teachers' understanding of the technology application model in schools and students' achievement.